Public-private mix for TB care and control - Uplekar, Mukund (Henry Stewart Talks, 2013)
Challenges of global TB control, Source of healthcare in South-East Asia and Sub-Saharan Africa, Non-qualified health providers, TB drugs sold in the private market, Why engage private care providers?, The public-private mix model, WHO's stop TB strategy, PPM contribution to case notifications in 2010 and 2011, Enhancing PPM with new technology, PPM guidance and tools, Challenges and approaches to scaling up
Archived at 2022/05/31